2015
DOI: 10.1007/s13593-015-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza symbiosis in viticulture: a review

Abstract: Viticulture is a major worldwide economic sector with a vine area of 7.52 million ha, wine production of 288 Mhl, and wine exports of 26 billion euros. Nevertheless, viticulture has to adapt to new challenges of pest management, such as pesticide reduction, and climate change, such as increasing droughts. Viticulture adaptation can benefit from arbuscular mycorrhiza, a plant-fungus symbiosis. Here, we review the ecosystemic services of arbuscular mycorrhiza for grapevine production. The major points are the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 177 publications
3
114
1
4
Order By: Relevance
“…, Maltz and Treseder , Tourvelot et al. ). Understanding the multiple benefits and costs of AMF in these projects is essential to their ultimate success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Maltz and Treseder , Tourvelot et al. ). Understanding the multiple benefits and costs of AMF in these projects is essential to their ultimate success.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing recognition that mycorrhizal fungi may be a critical component of forest management, agriculture, conservation, and restoration practices highlights the importance of a more complete view of the plant-AMF relationship (Moorman and Reeves 1979, Baum et al 2015, Maltz and Treseder 2015, Tourvelot et al 2015. Understanding the multiple benefits and costs of AMF in these projects is essential to their ultimate success.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effects of tillage on mycorrhiza in vineyards are scarce. For example, Trouvelot et al (2015) found that vegetated inter-rows favour arbuscular mycorrhizal fungi in the soil and roots of grapevines. Thus, effects of tillage on soil biota will consequently also support ES-like nutrient cycling and soil formation (Brussaard, de Ruiter, & Brown, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most perennial crops are mycorrhizal, forming a root symbiosis with fungi, e.g., apple (Gnekow and Marschner 1989), citrus (Menge et al 1978), olive (Roldán-Fajardo and Barea 1985), raspberry (Taylor and Harrier 2000), and grape (Trouvelot et al 2015). This mutualism confers many benefits to hosts, particularly nutritional and stress tolerance (Smith and Read 2008), but is threatened in most agricultural systems due to management activities that inhibit the fungi such as tillage (Brito et al 2012), fungicide use (Graham et al 1986), and some forms of weed control (Schreiner et al 2001).…”
Section: Mycorrhizal Fungimentioning
confidence: 99%